The characterization and evaluation of cisplatin-loaded magnetite–hydroxyapatite nanoparticles (mHAp/CDDP) as dual treatment of hyperthermia and chemotherapy for lung cancer therapy. Issue 2 (March 2015) - Huang, Jian-Yuan; Chen, Min-Hua; Kuo, Wei-Ting; Sun, Yu-Jun; Lin, Feng-Huei
Abstract: In this study, cisplatin (CDDP)-loaded magnetite–hydroxyapatite (mHAp/CDDP) nanoparticles were synthesized, characterized, and further evaluated for efficacy in chemotherapy and hyperthermia based combination therapy against lung cancer. The loading efficiency of the cisplatin in the synthesized nanoparticles was 22.9%. The major phase of the synthesized mHAp/CDDP nanoparticle was identified as hydroxyapatite by XRD pattern, with the magnetite and CDDP crystal precipitated on the surface of hydroxyapatite along [211] and [200], respectively. The grain size, determined by TEM, was in the range of 50–80 nm. The superconducting quantum interference device (SQUID) revealed that the nanoparticle possessed a superparamagnetic property and an alternating magnetic field acting upon that could induce heat within the body for hyperthermia in minutes. The synthesized nanoparticles were engulfed by cells through endocytosis. The loaded cisplatin was released due to the breakdown of the endosome–lysosome hybrid causing A549 cells to undergo apoptosis via ERK signaling pathway. The combination of hyperthermia and chemotherapy in one nanoparticle could provide a synergistic effect against A549 proliferation and tumor growth. We believe that mHAp/CDDP nanoparticles have great potential for lung cancer treatment.